SOSIALIASI RUBELLA, PENCEGAHAN, DAN DETEKSI DININYA PADA KADER KESEHATAN DI MOJOKERTO - Anindya Hapsari; Tika Dwi Tama; Dian Mawarni (Universitas Pahlawan Tuanku Tambusai, 2022)
Rubella virus is one of virus that when infect pregnant women can lead to disability in infant called Congenital Rubella Syndrome. However, the preventive and early detection programmes of rubella through MR vaccination and surveillance haven’t carried out routinely. That’s why people need to aware by increasing their knowledge. This community service aimed to increase the knowledge of voluntary health workers (kader kesehatan) in Polindes Nusa Indah Mojokerto about rubella, its prevention, and its early detection. An offline education involved 34 voluntary health workers. The evaluation method used was comparing pretest and posttest score. The results showed that there was an increasing score after the education was given, which the mean of pretest score was 41.76 compared to 81,18 of posttest score. Statistical analysis showed p-value < 0.05 means that there was a difference of knowledge before and after the education was given. The conclusion was education given by this community service is quite effective in increasing the knowledge of voluntary health workers about rubella, its prevention, and its early detection. So it is hoped that after this community service, the voluntary heatlh workers can educate people, recognize, and detect rubella early so that this disease won’t be spreaded. Keywords: rubella education, voluntary health worker, increasing of knowledge